Interoperabilidade e análise de estrutura não convencional de concreto armado - Pitanga, Allan Pires (2023)
With the increasingly faster processing speed of computers available to the wide public, computational tools facilitated access to important possibilities in the conception and modeling of architectural projects: complex forms, which are not described by basic geometric forms; and generative systems, which allow the manipulation of shapes with speed and precision. With the growing application of these new design tools in the market, the interoperability, or compatibility between architectural modeling and structural analysis programs and the possibility of exchanging information between software, directly influences the quality and speed of a design. This article proposes the structural analysis of an unconventional reinforced concrete building, which has a higher level of complexity than usual residences and buildings. Through the use of the Autodesk Revit 2023.2 and Robot Structural Analysis Professional 2023 softwares, it was possible to verify the limitations of some functionalities found in the integration between the software when dealing with nonconventional forms, as well as the inconsistencies in the structural model resulting from the integration, which were corrected with resources available in Robot. With the obstacles circumvented, it was possible to analyze the behavior of an unconventional structure of reinforced concrete, as well as to interpret the results presented by the program, in order to properly determine the reinforcement of the structure based on the working stresses.